Syntheses, structures and luminescent properties of four zinc(II) coordination polymers constructed from mixed isophthalic acid and flexible unsymmetrical bis(pyridyl) ligands. (14th December 2015) - Zhao, Shu-Nan; Deng, Zhao-Peng; Zhang, Zhu-Yan; Huo, Li-Hua; Gao, Shan
Graphical abstract: Four mixed-ligands compounds assembled from four flexible unsymmetrical bis(pyridyl) ligands were synthesized and characterized, which exhibit linear chain, double chain, (4, 4) layer, as well as layer structure with (4·6 4 ·8)2 (4 2 ·6 4 ) topology. Abstract: The reaction of zinc(II) salts, isophthalic acid, and four flexible unsymmetrical bis(pyridyl) ligands, namely, N -(pyridin-2-ylmethyl)pyridin-2-amine (L1), N -(pyridin-2-ylmethyl)pyridin-3-amine (L2), N -(pyridin-4-ylmethyl)pyridin-2-amine (L3), and N -(pyridin-4-ylmethyl)pyridin-3-amine (L4), gives rise to four compounds, [Zn(ip)(L1)] n (1 ), [Zn(ip)(L2)] n (2 ), [Zn3 (ip)3 (L3)2 ] n (3 ), and [Zn(ip)(L4)] n (4 ), which have been characterized by elemental analysis, IR, TG, PL, powder and single-crystal X-ray diffraction. Adjacent four- and five-coordinated Zn(II) cations in compounds1 and2 are joined by the ip dianions in μ 2 ( κ 1 O: κ 1 O) and μ 3 ( κ 1 O: κ 1 O: κ 1 O: κ 1 O) modes to form single and double chains. In contrast, the ip dianions in compound3 act in μ 3 ( κ 1 O: κ 1 O: κ 1 O: κ 1 O) and μ 4 ( κ 1 O: κ 1 O: κ 1 O: κ 1 O) modes to bridge three types of zinc(II) polyhedra (four-, five- and six-coordinated), thus generating layer motif with (4·6 4 ·8)2 (4 2 ·6 4 ) topology. Compound4 presents (4, 4) layer motif which is formed by the interconnection of zinc(II) tetrahedral through μ 2 ( κ 1 O: κ 1 O) ip dianions and anti -L4 ligands. The four bis(pyridyl) ligands in these compounds present diverse syn- and anti -conformations, which are responsible for the diversities of supramolecular networks. Moreover, solid-state luminescent properties demonstrate that the four compounds exhibit stronger emission intensities from 383 to 527 nm at room temperature.